Individual or Community? Two Approaches to Ecophilosophy in Practice. (1st May 1992) - Rothenberg, David
Should environmental philosophers Ð or practical conservationists Ð focus their attentions on particular living creatures, or on the community of which they, and we, are part? The individualist ethos of the United States is reflected in legislation to protect endangered species in which particular species are portrayed as individuals with rights that must be protected. By contrast, the planning of environmental protection in Norway, exemplified by the Samla Plan for the management of water resources, emphasizes the importance of community integrity, where 'community' includes the whole of nature. These differing approaches are considered in the light of moral monism and pluralism, with special reference to Christopher Stone's recent work. Despite their differences, and the reservation that each method inevitably takes a human perspective, it can be hoped that each may contribute to enabling people and political systems to consider nature more seriously.